2021
DOI: 10.3389/fpubh.2021.728690
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 Vaccine Hesitancy: A Cross-Sectional Study on a Mexican Population Using an Online Questionnaire (COV-AHQ)

Abstract: Mexico has become one of the most highly affected countries by coronavirus disease 2019 (COVID-19) pandemic in Latin America. Therefore, efficient vaccination programs are needed to address COVID-19 pandemic. Although recent advances around the world have made it possible to develop vaccines in record time, there has been increasing fear and misinformation around the vaccines. Hence, understanding vaccine hesitancy is imperative for modeling successful vaccination strategies. In this study, we analyzed the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 28 publications
(39 reference statements)
2
31
1
4
Order By: Relevance
“…This shows that appropriate levels of danger and contamination fears may be imbued into information on COVID-19 vaccination by health professionals and educators to help influence adolescents' acceptance of vaccination. In fact, a previous study revealed that danger and contamination concerning COVID-19, irrespective of the severity (i.e., mild, moderate, and severe), positively influenced COVID-19 vaccination intent [62]. Moreover, traumatic stress, another subscale of COVID-19 stress, was found to negatively predict COVID-19 vaccination acceptance.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This shows that appropriate levels of danger and contamination fears may be imbued into information on COVID-19 vaccination by health professionals and educators to help influence adolescents' acceptance of vaccination. In fact, a previous study revealed that danger and contamination concerning COVID-19, irrespective of the severity (i.e., mild, moderate, and severe), positively influenced COVID-19 vaccination intent [62]. Moreover, traumatic stress, another subscale of COVID-19 stress, was found to negatively predict COVID-19 vaccination acceptance.…”
Section: Discussionmentioning
confidence: 87%
“…Measurement scales have been developed to assess COVID-19 vaccination acceptance [49][50][51][52], which have helped researchers to objectively examine COVID-19 vaccination acceptance in various countries. Factors influencing COVID-19 vaccinations seem to be wide and varied, from external factors such as the culture, political governance, gross domestic product, and inter-country relationships [53][54][55][56][57][58][59][60][61] to internal or personal factors such as age, sex, educational levels, profession, and lifestyle behaviours [53,54,[56][57][58]61,62]. For instance, previous studies have reported sex differences in COVID-19 attitudes and behaviours [63,64], leading to sex differences in COVID-19 infection [65], although other studies revealed contradictory findings on COVID-19 vaccine acceptance [61,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…The present study derives from the application of the online COVID-19 Vaccine Acceptance & Hesitancy Questionnaire, or COV-AHQ (Cronbach’s alpha > 0.8) [ 27 ], which was designed based on the initial and Adapted COVID-19 Stress Scales (CSS and ACSS) [ 28 , 29 , 30 ] and the Vaccine Hesitancy Scales (VHS) [ 22 ]. For the present study, we took into consideration only the subpopulation of participants with the criteria of answering yes to having children.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the available scales had adapted existing surveys related to perspectives on general vaccine hesitancy or childhood vaccination. 17 , 37 , 38 Those scales that were developed specifically for COVID-19 vaccines have limitations, including wording that is outdated in light of the current availability of a vaccine (e.g., “If a COVID-19 vaccine was available at my local pharmacy, I would … ”), 16 not considering specific COVID-19 vaccine concerns, 19 only focusing on one aspect of concerns (adverse effects of the vaccine), 20 or being lengthy. Our survey adds to these resources by providing a succinct tool to assess topics specifically relevant to our evolving discovery of individuals’ perspectives that impact COVID-19 vaccine hesitancy, such as the role of existing immunity, new vaccine technology, and conspiracy theories.…”
Section: Discussionmentioning
confidence: 99%
“…However, while these measures assess one’s hesitancy to get vaccinated, they do not provide an understanding of the root causes of COVID-19 vaccine hesitancy. Some recent scales have been developed that include items to examine contributors to COVID-19 vaccine hesitancy, 20 , 21 but thus far, items in these scales tend to be those that are common to general vaccine hesitancy (e.g., adverse reactions, side effects) and not reflective of the nuanced hesitancy that surrounds COVID-19 vaccines.…”
mentioning
confidence: 99%